2023
DOI: 10.3389/fsurg.2023.1209927
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery as a new clinical standard for bone anchored hearing implants—real-world data from 10 years of follow-up and 228 surgeries

Abstract: PurposeTo explore the clinical practice development of different surgical techniques when installing bone-anchored hearing implants and their associated trends in outcomes.DesignRetrospective study of 228 bone-anchored hearing implants in 200 patients, performed over a 10-year period between 2012 and 2022 in a referral hospital.MethodReal-world data of demography, etiology, surgical setup, complications, and audiological outcomes were collected. Eligibility criteria from clinical practice were applied.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With regard to the surgical methods, our study suggests that the MIPS method is associated with improved implant stability compared to linear incision traditional approach with Baha or Ponto surgery. A recent study evaluating BAHIs in over 200 patients demonstrated that MIPS is associated with shorter surgery duration compared to linear incision (20 versus 44 min) and that MIPS had a relatively lower rate of complications (intraoperative; 1.8% versus 4.9%, postoperative; 49% versus 66%), with most complications being related to skin and wound healing (18). Moreover, MIPS and linear incision approaches have different drilling protocols that may affect implant stability.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the surgical methods, our study suggests that the MIPS method is associated with improved implant stability compared to linear incision traditional approach with Baha or Ponto surgery. A recent study evaluating BAHIs in over 200 patients demonstrated that MIPS is associated with shorter surgery duration compared to linear incision (20 versus 44 min) and that MIPS had a relatively lower rate of complications (intraoperative; 1.8% versus 4.9%, postoperative; 49% versus 66%), with most complications being related to skin and wound healing (18). Moreover, MIPS and linear incision approaches have different drilling protocols that may affect implant stability.…”
Section: Discussionmentioning
confidence: 99%